1인가구 생활패턴이 반영된 세탁O2O서비스 사용성 평가 연구 -런드리고와 세탁특공대를 중심으로 - 정자영; Jeong¸ Ja Young; 장경국; Chang¸ Kyoung Kook (기초조형학연구, 2021)
최근 1인가구 증가와 타임푸어족의 등장으로 세탁 O2O 서비스의 이용률이 높아지고 있다. 본 연구는, 세탁 O2O 서비스인 런드리고와 세탁특공대 애플리케이션을 중심으로 사용성 평가 비교분석을 통해 향후 20~30대 1인가구를 위한 세탁 O2O 서비스 사용성 개선을 위한 필요사항을 도출하고 의(衣)활동 이론 발전에도 기여하는데 목적이 있다. 연구방법으로는 1차로 문헌연구를 통해 1인가구의 현황, 라이프스타일, 세탁 O2O서비스의 시장 현황 및 전망 등을 고찰하였으며, 2차로 사용성 평가를 위해 피터모빌(Peter Morville)의 허니콤 모델(The Honeycomb Model) 7가지 요소를 기초하여 1인가구의 전체비율 중 가장 많은 비중을 차지하고 있는 20~30대 남녀를 대상으로 심층인터뷰를 진행 하였다. 사용성 평가 결과, 전체적으로 세탁특공대 앱의 서비스 사용성이 더 높은 것으로 나타났다. 특히 사용성, 가치성에 있어서는 1) 세탁물을 맡기고 수거하는 과정에 있어서 시간이 단축되는 점. 2) 출퇴근 시간에 제약 없이 사용가능한 점. 3) 빨래를 해야 하는 귀찮음을 해소했다는 점에 대하여 두 애플리케이션 모두 20~30대 1인가구 피실험자들에게 높은 평가를 받았다. 이러한 사용성 평가를 바탕으로 다음과 같은 개선점을 얻을 수 있었다. 첫째, 각 세탁 건별에 대한 평가와 업체에 대한 평가가 필요하다. 둘째, 그 평가에 따른 피드백 서비스가 필요하다. 셋째, 개인정보보호를 강화하여 신뢰성을 높여야 한다. 본 연구 결과를 통해 국내 세탁 O2O 서비스 향상에 기여하기를 기대하며, 향후 연구에서는 보다 폭넓은 1인가구의 연령층을 분석하여 1인가구의 의(衣)활동 발전에 기여할 수 있는 사용성 연구가 나오기를 기대한다. As the number of one-person households and the Timepoors has arisen in recent years, the utilisation rate of laundry O2O services is increasing. The purpose of this study is to derive the need to improve the usability of laundry O2O services for one-person households in their 20s and 30s and contribute to the development of clothing activity theory through comparative analysis of usability evaluation focused on the mobile application ‘Laundrygo’ and ‘Getwashswat’ application. A literature study examined the current status of one-person households, there’s lifestyle, market status and prospects of laundry O2O services. In addition, based on seven elements of Peter Morville's User Experience Honeycomb, an in-depth interview was conducted for those in their 20s and 30s, which account for the highest proportion of one-person households. As a result of the usability evaluation, the ‘Getwashswat’ application has higher service usability than ‘Laundrygo’. Especially in the field of usable and valuable, both applications received high scores from one-person households in their 20s and 30s for the following reasons : 1) Time reduction in the process of drop-off and collecting laundry. 2) Unlimited use during rush hour. 3) Hassle-Free from Laundry. Based on this usability assessment, the following improvement results were obtained through the data analysis : First, evaluation on the service supplier and laundry case is required. Second, feedback services according to the assessment are needed. Third, it is necessary to increase reliability by strengthening privacy. The results of this study are expected to lead to improving domestic laundry O2O services. In future studies, researcher hopes to analyse the whole age group of one-person households to contribute to the development of clothing activities in one-person households.